Pengaruh Tax Compliance Pelaporan Surat Pemberitahuan Terhutang (Spt) Tahunan Pegawai Di Lingkungan Universitas Musamus Dengan Sosialisasi Sebagai Variabel Moderasi - Epin, Maria Natalia Wainip; Allo, Cici Girik (Jurnal Akuntansi Bisnis Pelita Bangsa, 2024)
The aim of this research is to analyze tax compliance reporting of outstanding notification letters (SPT) of employees at Musamus University with socialization as a moderating variable. The data collection method uses a questionnaire. This research uses 100 employee taxpayers as a sample selected using a random sampling method. The analysis technique in this research uses Partical Least Square (PLS). Based on the results of data analysis carried out using Partical Least Square (PLS), it was found that the e-filing variable (SPT reporting) had a significant effect on the tax compliance value, while the tax compliance variable was reporting outstanding notification letters (SPT) for employees at Musamus University with socialization as The moderating variable is unable to moderate the relationship between tax socialization and tax compliance with employee SPT reporting. It is hoped that the results of this research can contribute academically and practically.